Optimizing the Use of Meninting Multipurpose Reservoir Water in West Lombok District - Rediasti, Fransisca Natania Karina; Jayadi, Rachmad; Triatmodjo, Bambang (Journal of the Civil Engineering Forum, 2023)
The construction of the Meninting Reservoir was planned with the objective of meeting the irrigation and domestic water demands on Lombok Island. It served as a multipurpose reservoir, with a maximum storage volume of 12.18 million m³, mainly for supplying irrigation and domestic water. The reservoir had considerable potential for water availability, which could be used to supply water to the South Lombok region with limited water availability but had agricultural land potential. Therefore, this study aimed to evaluate the potential of Meninting Reservoir water availability and its optimum utilization for irrigation and domestic purposes. The irrigation water demand for 1,559.29 ha and domestic water demand of 150 ls-1 was fulfilled by Meninting Reservoir. Water availability in this Reservoir was estimated with the F.J. Mock method of rainfall-runoff model using 25 years of daily rainfall data from Gunung Sari and Sesaot rain gauge stations. The calibration process of the rainfall-runoff parameters models employed observed discharge data from the Aiknyet water level gauge station. The formula for optimizing reservoir water release was prepared using the linear programming method based on operational water level limits, inflow discharge, irrigation, and non-irrigation water requirements, including domestic water. The optimal average annual cropping intensity was 203.96%, 215.87%, and 241.41% for dry, normal, and wet years, respectively. The service reliability of irrigation and domestic water demands reached 100% for all inflow discharge conditions. The k-factor value met the minimum limit of 0.70 and 0.85 for irrigation and domestic water demands, respectively.